Sistem Informasi Penjualan Menggunakan Metode User Centered Design (UCD) Berbasis Web pada Icikiwir Distro - Pramesti, Adinda Ayu Mega; Ikhwan, Ali (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Icikiwir Distro Shop is a trading business operating in the fashion sector, which only started selling in 2012, located on Jalan Besar Negeri Lama, Bilah Hilir District, Labuhan Batu Regency. The Icikiwir Distro Shop sells various kinds and types of clothing, socks, hair oil, hats, shoes and other things, and accepts screen printing orders. Currently, the media used at the Icikiwir Distro Shop is putting up banners on the Icikiwir Distro Shop, and for social media for the Icikiwir Distro Shop, namely using Instagram, WhatsApp and Facebook. The problem is that in marketing new products or old products, many consumers do not yet know widely about what items can be found at the Icikiwir Distro Shop. Due to current problems, the Icikiwir Distro Store requires an increase in item display to increase customers and increase store income. The online sales information system is one of the advances in innovation and the web. Web access is used to trade on the web. Data frameworks are one of the important things to help business progress. Therefore, to overcome promotional problems at the Icikiwir Distro Store, it is necessary to create a web-based information system that can further develop the implementation of officers, stock administration and report preparation which can develop the system which has been running manually to become more modern. The strategy used in this exploration is the User Centered Design UCD method). The User Centered Design (UCD) method is an iterative connection point configuration process approach that highlights comfort targets, user quality, environment, assignments, and work processes in the plan.